Anti-cancer natural products isolated from chinese medicinal herbs - Wu Guosheng; Chen Meiwan; Li Yingbo; Huang Mingqing; Lu Jinjian; Tan Wen; Gong Jian; Zhong Zhangfeng; Xu Zengtao; Dang Yuanye; Guo Jiajie; Chen Xiuping; et al. (BMC, 2011)
Abstract In recent years, a number of natural products isolated from Chinese herbs have been found to inhibit proliferation, induce apoptosis, suppress angiogenesis, retard metastasis and enhance chemotherapy, exhibiting anti-cancer potential both in vitro and in vivo. This article summarizes recent advances in in vitro and in vivo research on the anti-cancer effects and related mechanisms of some promising natural products. These natural products are also reviewed for their therapeutic potentials, including flavonoids (gambogic acid, curcumin, wogonin and silibinin), alkaloids (berberine), terpenes (artemisinin, β-elemene, oridonin, triptolide, and ursolic acid), quinones (shikonin and emodin) and saponins (ginsenoside Rg3), which are isolated from Chinese medicinal herbs. In particular, the discovery of the new use of artemisinin derivatives as excellent anti-cancer drugs is also reviewed.